A Cross-Sectional Study to Evaluate the Association of HbA1c and Triglycerates HDL Ratio as a Non Invasive Marker in Non Alcoholic Fatty Liver Disease in a Tertiary Center - E, Pravinraj; V. R, Mohan Rao; Raksha, Sai (Journal of Neonatal Surgery, 2025)
Introduction Non-alcoholic fatty liver disease (NAFLD) is distinguished by the presence of excess fat deposits within hepatic cells specifically when 5% or more of hepatocytes contain fat, by eliminating secondary causes such as excessive alcohol consumption or medications. It is a globally leading liver disease, affecting adults over 25%, with rising prevalence due to increasing obesity, type 2 diabetes mellitus and metabolic syndrome. This study explores HbA1c levels and the triglyceride-to-HDL ratio as non-invasive diagnostic markers. Materials and Methods: This cross-sectional study aims to correlate an association between HbA1c and the triglyceride to HDL ratio in the context of non-invasive NAFLD diagnosis. Conducted at a tertiary care center in Chengalpattu district, the study used a convenient sampling method with 85 participants aged 18–65 years, including those with comorbidities like diabetes, dyslipidemia, and hypertension. Data analysis was calculated with the help of SPSS version 21, and the chi-square test, utilized to assess the relationships between the variables Results: Participants mean age in this study was 53.57 ± 14.0. 31 patients were in the grade 1 and 27 patients in Grade 2 and 3 respectively. Most of the patients were having high TGL:HDL and grade III fatty liver (n=21). A significant association was noted among the TGL:HDL cholesterol ratio and grade of liver steatosis (p = 0.038). Higher level of HbA1c was associated with increased grading of fatty liver. 19 patients with HbA1c >6.5 were having grade III fatty liver, 16 patients with HbA1c 6.1-6.4 had grade II fatty liver. No significance was demonstrated between HbA1c and grade of fatty liver (p=0.692). Conclusion: The triglyceride to HDL-C ratio and HbA1c are potential non-invasive biomarker for NAFLD, linked to insulin resistance and lipid metabolism. It is accessible, easy to use, and aids early detection. Further more researches are needed to confirm its broader clinical applicability, while it may enhance early diagnosis and management